Application of Multimodal Multimedia Information and Big Data Technology in Teaching Chinese as a Foreign Language Course - Yanhua Nie (International Journal of Digital Multimedia Broadcasting)
With the change of the times, under the leadership of big data, cloud computing, network technology, mobile Internet, and other high technology, education has gradually broken free from the traditional teaching mode. At the same time, advanced technology has also lifted the confinement of traditional teaching mode in space and time and opened the skylight of intelligent thinking mode. From the current situation of Chinese language fever around the world, the demand of Chinese language learners for learning materials and learning resources will continue to increase in the future. With the continuous development of Internet education, the combination of Internet technology and international Chinese education will definitely become the key direction for the development of international Chinese education. In this context, online teaching resources will become an important basis for the development of “Internet+Chinese international education”, so it is necessary to investigate and study the online teaching resources of “Internet+Chinese international education.” As a matter of fact, with the development of society and the advancement of technology, the era of informationization has come. As a result, the main theme of education in the information age is to provide suitable education for students who want to learn Chinese and to promote the active and lively development of each student. In the past, the one-size-fits-all education model of classroom teaching could not meet the individual development of students and the demand of society for diversified talents. Therefore, the traditional teaching of Chinese as a foreign language is in urgent need of change, and personalized teaching is attracting attention. With the emergence of technologies such as cloud computing, Internet of Things, and big data in education, personalized teaching has received technical support. This paper is aimed at exploring how to apply the new technologies in the teaching process to help teachers personalize teaching, stimulate students’ interest in learning, meet their individual needs, break through the traditional teaching methods, and make it possible to teach according to their abilities. As one of the main learning resources, the quality of multimedia courseware will be the criterion to measure whether it meets the teaching and learning needs. Consequently, the use of big data, multimedia, and multimodal technologies to improve the Chinese language material library and develop special software for teaching Chinese as a foreign language, as well as the production of high-quality multimedia courseware that is highly compatible with the teaching materials, will become the trend of future research.